Pengaruh Word of Mouth dan Influencer Marketing Terhadap Keputusan Pembelian Kacamata di Optik Jaya Kota Padang - Amril, Alwa Pascaselnofra; Wesnita, Alvia; Suryanta, Dolly Iman (LPPM Universitas Dharma Andalas, 2025)
This study aims to analyze the influence of Word of Mouth (WOM) and Influencer Marketing on the purchasing decision of eyeglasses at Optik Jaya, Padang City. A quantitative approach was employed using a survey method involving 76 active customers as respondents. Data were analyzed using multiple linear regression to assess both simultaneous and partial effects of the independent variables. The findings indicate that both Word of Mouth and Influencer Marketing have a positive and significant effect on purchasing decisions. WOM contributes through interpersonal information credibility, while Influencer Marketing influences through the attractiveness and social power of public figures on social media. Together, these variables account for 37.4% of the variation in consumer purchasing decisions. These results provide practical implications for optical businesses in designing marketing strategies that integrate interpersonal and digital communication to enhance customer loyalty and sales volume.